1996
DOI: 10.1159/000276862
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sinusitis Signs in a Non-ENT Population

Abstract: Relatively little is known about the prevalence of sinusitis in a general population. Patients with suspected intracranial neurological disease can be considered as representative of the general population. On magnetic resonance imaging nearly 60% of the sinuses were affected. If the most common lesion (a maxillary polyp or cyst) was excluded, still 40% of the sinuses were affected. Above all the maxillary sinuses are involved with 40% abnormal images followed by the anterior ethmoidal sinuses with 14%. The ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
51
3
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 8 publications
9
51
3
7
Order By: Relevance
“…Diamant et al [5] found maxillary and ethmoidal thickening in 50% of patient. Similar figures were found by Gordts et al [6,7] who demonstrated in an MRI study of a non-ENT population of adults that there existed on 40% abnormalities of the mucosa, and in 45% of the cases in a non-ENT population of children.…”
Section: Introductionsupporting
confidence: 85%
“…Diamant et al [5] found maxillary and ethmoidal thickening in 50% of patient. Similar figures were found by Gordts et al [6,7] who demonstrated in an MRI study of a non-ENT population of adults that there existed on 40% abnormalities of the mucosa, and in 45% of the cases in a non-ENT population of children.…”
Section: Introductionsupporting
confidence: 85%
“…Prevalence for sensitization to inhalant allergens is reported in up to 84% of patients undergoing revision sinus surgery (2102). Compared to the general population where CRS is estimated to be found in up to 6% of subjects (2103)(2104)(2105)(2106), patients sensitized to inhalant allergens seem to experience more sinus complaints. On the basis of these epidemiologic observations, one may not however conclude that allergic rhinitis predisposes to the development of CRS as these studies include a large referral bias.…”
Section: Rhinosinusitismentioning
confidence: 99%
“…При этом следует отметить, что истинная заболе-ваемость РС и у детей, и у взрослых неизвестна, так как в большинстве случаев вирусный РС не диагностируется в качестве самостоятельного заболевания, а рассматривает-ся как проявление острой респираторной вирусной ин-фекции (ОРВИ) [1,2].Исследования с использованием КТ и МРТ выявили признаки РС в 95% случаев острого респираторного забо-левания [3][4][5]. Среди основных вирусов-возбудителей ОРС называют риновирус, респираторно-синцитиаль-ный, аденовирус, коронавирус, некоторые исследователи включают в этот перечень и вирус парагриппа [1][2][3]5].…”
unclassified
“…Исследования с использованием КТ и МРТ выявили признаки РС в 95% случаев острого респираторного забо-левания [3][4][5]. Среди основных вирусов-возбудителей ОРС называют риновирус, респираторно-синцитиаль-ный, аденовирус, коронавирус, некоторые исследователи включают в этот перечень и вирус парагриппа [1][2][3]5].…”
unclassified
See 1 more Smart Citation